2007
DOI: 10.1097/md.0b013e318045a00e
|View full text |Cite
|
Sign up to set email alerts
|

Wilson Disease

Abstract: The clinical manifestations of Wilson disease (WD) are varied and challenging. We conducted the current study to present the phenotypic characteristics and follow-up for a large cohort of patients with WD. We reviewed the medical records of 282 cases of WD (male:female ratio, 196:86) for clinical features, investigations, treatment, and outcome data. The clinical presentations were as follows: hepatic, 42 (14.9%); hepato-neurologic, 10 (3.5%); neurologic, 195 (69.1%); pure psychiatric, 7 (2.4%); osseomuscular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(101 citation statements)
references
References 29 publications
5
92
2
2
Order By: Relevance
“…The accumulation of copper in liver results in copper overload in the brain, inducing neurological Wilson disease. A study on the clinical presentations of this disease (282 cases) showed that 69% of patients were classified as having neurological Wilson disease (50). The predominant neurological features were Parkinsonism, 62.3%; dystonia, 35.4%; cerebellar, 28%; pyramidal signs, 16%; chorea, 9%; athetosis, 2.2%; myoclonus, 3.4%; and behavioral abnormalities, 16% (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of copper in liver results in copper overload in the brain, inducing neurological Wilson disease. A study on the clinical presentations of this disease (282 cases) showed that 69% of patients were classified as having neurological Wilson disease (50). The predominant neurological features were Parkinsonism, 62.3%; dystonia, 35.4%; cerebellar, 28%; pyramidal signs, 16%; chorea, 9%; athetosis, 2.2%; myoclonus, 3.4%; and behavioral abnormalities, 16% (50).…”
Section: Discussionmentioning
confidence: 99%
“…A study on the clinical presentations of this disease (282 cases) showed that 69% of patients were classified as having neurological Wilson disease (50). The predominant neurological features were Parkinsonism, 62.3%; dystonia, 35.4%; cerebellar, 28%; pyramidal signs, 16%; chorea, 9%; athetosis, 2.2%; myoclonus, 3.4%; and behavioral abnormalities, 16% (50). The fact that Parkinsonism is one of the major neurological symptoms in Wilson disease opens the question as to why the copper overload effect is specific for dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological manifestations can be categorized as: (1) an akinetic-rigid syndrome similar to Parkinson's disease; (2) pseudosclerosis dominated by tremor; (3) ataxia; and (4) a dystonic syndrome, which often leads to severe contractures [33,34] . Neuropsychiatric symptoms and signs, including decrease in scholastic performance, hand-eye discoordination, and behavioral changes may foretell a more florid neuro logical presentation [35] . Other findings include drooling, spasticity, chorea, athetosis, myoclonus, micrographia, dyslalia, hypomimia, and dysarthria [35,36] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Neuropsychiatric symptoms and signs, including decrease in scholastic performance, hand-eye discoordination, and behavioral changes may foretell a more florid neuro logical presentation [35] . Other findings include drooling, spasticity, chorea, athetosis, myoclonus, micrographia, dyslalia, hypomimia, and dysarthria [35,36] . Ocular mani festations include the KayserFleischer ring and sunflower cataracts in the lens, deposition of copper in the Descemet's membrane in the first case, and in the anterior and posterior capsule of the lens, sparing epithelial and cortical cells, in the latter [37,38] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Clinical manifestations predominantly reflect hepatic injury, but also include neuropsychiatric manifestations and hemolytic anemia [2]. A diagnosis of WD is supported by low ceruloplasmin, elevated hepatic copper, increased urinary copper excretion, and detection of Kayser-Fleischer rings on ophthalmologic examination [3].…”
Section: Introductionmentioning
confidence: 99%